Konseling Individual Dengan Teknik Pemberian Nasehat Dalam Memecahkan Masalah Kedisiplinan Siswa - Indri Yuli Wulandari; Suhertina Suhertina (Fakultas Tarbiyah dan Keguruan, 2020)
This research aimed at knowing the use of giving advices technique by guiding and counseling teacher on individual counseling services to solve student discipline problems and the factors influencing the use of giving advices technique on individual counseling services as to solve student discipline problems and the characteristics of student who were not discipline. The subjects of the research were 1 guiding and counseling teacher, and 3 students often violating disciplines. The object of the research was the individual counseling by giving advices technique in solving student discipline problems. The supporting informant of this research was 1 homeroom teacher. This research was a qualitative research with a case study design. Interview, observation and documentation techniques were used for collecting the data. Qualitative descriptive were used for analyzing the data. The finding of this research showed that the use of giving advices technique by guiding and counseling teacher on individual counseling services was that a way to direct students not violate disciplines. Giving advices technique was used by guidance and counseling teacher for students often violating disciplines– showing students both the better and worse behaviors. After giving advices, it was expected that students could make decisions for themselves, especially in solving discipline problems. The factors influencing the use of giving advices technique by guiding and counseling teacher on individual counseling services as to solve student discipline problems were caused by two factors–internal and external factors. Internal factors (from themselves) and from teacher him/herself, the teacher was not a graduate of guidance and counseling education. While the external factors ( family invironment), and characteristics of student who wer not discipline were such as student often come late, sleep in classroom, come late, doing homework at school and lack attention to the teacher explanation.